Comparative Analysis of the Way of Financing of Greek and Romanian Heathcare System - Kanellopoulos, Dimitrios (Richtmann Publishing, 2012)
The purpose of this review is to study the way of financing of the Romanian and Greek health system .For that purpose we aredoing a general reference to the way of financing of health systems, and then a reference on ways of funding of Health Care systemin Greece and Romania. The concept of financing can be identified as the need to find resources and sharing them. In the case of healthsystems, the concept includes the origin of sources, methods of financing, the management of sources and finally the criteria of theirallocation. The scope of this paper is to analyze the way of financing of both health systems.